Extracellular Reduction of Cat1 Free Radical by Transformed Human Hepatocytes. Issue 6 (December 1998) - Bernas, Tytus; Dobrucki, Jurek
Abstract : Redox activities associated with plasma membranes of nonphagocytic animal and plant cells have been reported by several authors. However, the natural substrates, structure and biological role of these putative enzyme systems are not known. Data indicating extracellular reduction of a nitroxide free radical Cat1 (1-oxy-4-trimethylamine-2, 2, 6, 6, tetramethyl-piperidine) by hepatocytes were thought to be artefactual. We report evidence in support of a notion that Cat1 as well as a tetrazolium salt, CTC (5-cyano-2, 3-ditolyl tetrazolium chloride), are reduced extracellularly, probably at the cell surface, by human HepG2 hepatoma cells. These data provide evidence confirming the existence of a yet unidentified reducing activity associated with outer surface of plasma membranes of transformed human hepatocytes.